Discovery of N-substituted 7-azaindoles as Pan-PIM kinases inhibitors – Lead optimization – Part III. Issue 3 (1st February 2019) - Barberis, Claude; Pribish, James; Tserlin, Elina; Gross, Alexandre; Czekaj, Mark; Barragué, Matthieu; Erdman, Paul; Maniar, Sachin; Jiang, John; Fire, Luke; Patel, Vinod; Hebert, Andrew; et al.
Graphical abstract: Abstract: N -substituted azaindoles were discovered as promising pan-PIM inhibitors. Lead optimization is described en route toward the identification of a clinical candidate. Modulation of physico-chemical properties allowed to solve inherent hERG and permeability liabilities. Compound 17 showed tumor growth inhibition in a KG1 tumor-bearing mouse model.